2021
DOI: 10.1186/s42466-021-00106-3
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in neurological diseases

Abstract: Insomnia is defined as difficulties of initiating and maintaining sleep, early awakening and poor subjective sleep quality despite adequate opportunity and circumstances for sleep with impairment of daytime performance. These components of insomnia – namely persistent sleep difficulties despite of adequate sleep opportunity resulting in daytime dysfunction - appear secondary or co-morbid to neurological diseases. Comorbid insomnia originates from neurodegenerative, inflammatory, traumatic or ischemic changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 104 publications
1
3
0
1
Order By: Relevance
“…According to the published articles, this study supports research (Mayer et al, 2021;Smitherman et al, 2018) that found a correlation between poor sleep and primary headaches, particularly migraine without aura and TTH. According to this study, 48.9% of the study sample who had TTH also had primary headaches, making up 67.8% of those with poor sleep quality.…”
Section: Discussionsupporting
confidence: 88%
“…According to the published articles, this study supports research (Mayer et al, 2021;Smitherman et al, 2018) that found a correlation between poor sleep and primary headaches, particularly migraine without aura and TTH. According to this study, 48.9% of the study sample who had TTH also had primary headaches, making up 67.8% of those with poor sleep quality.…”
Section: Discussionsupporting
confidence: 88%
“…Even if doxepin and amitriptyline are not considered as a first choice for the treatment of depression, they offer further valuable effects concerning symptoms of insomnia, neuropathic pain, chronic headache and spastic pain in combination with sleep and anxiety disorders, which can occur in patients with MS together with additional symptoms of depression [ 28 , 29 , 30 , 31 , 72 ]. The advantage of the old antidepressants is that they are not selective, as with the modern serotonin re-uptake inhibitors, but have more effects.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were included in the study if they reported: (a) being aged 18-35 years old, (b) not suffering from a sleep disorder (e.g., insomnia) or psychiatric disorder (e.g., PTSD, major depression or substance use disorder), (c) not taking medication for such disorders, (d) being regular sleepers, sleeping between 7 and 9 h a night, (e) not suffering from any medical or neurological condition (e.g., head injury) known to influence sleeping, dreaming or emotional and cognitive functioning, (f) having access to a laptop/computer, phone and a stable internet connexion. Criteria (a)-(e) are all known to influence, sleep, emotional memory processing or dreaming (Krystal, 2012;Cherdieu et al, 2014;Park et al, 2015;Conte et al, 2021;Mayer et al, 2021).…”
Section: Eligibility Criteriamentioning
confidence: 99%